Peningkatan Kapasitas Pemuda Desa Alu - Rahmatullah Rahmatullah; Aco Nata Saputra; Hendrawan Hendrawan; Muhammad Syihabuddin Taufiq (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract Increasing optimal youth capacity can have a positive impact on improving the welfare of village communities. To realize this achievement, it is necessary to carry out village youth training, including carrying out training and intellectual development of village youth. There are several stages carried out, namely: 1) carrying out training with several members of the village youth academy; and 2) compiling a report on the results of the analysis that is useful as material in managing youth organizations at the village level. Implementation of community service related to developing youth capacity in organizational development is carried out offline or face to face. The results of the analysis of increasing youth capacity show that there is a lot of youth potential that can be developed by collaborating with stakeholders involved in village development.